A survey on android security: development and deployment hindrance and best practices - Ratul Sikder; Md Shohel Khan; Md Shohrab Hossain; Wazir Zada Khan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Android OS is the most popular mobile OS for the past few years. Vulnerabilities arise with respect to the increasing functionality of Android OS, impolitic app development practices of developers, end-user incautious and interestingly remediation for the vulnerabilities has been introduced frequently as well. To mitigate security risk factor Google has been updated, deprecated and restricted many system level APIs for 3rd party developers. Considering the consequences, this paper provides a wide overview of Android’s system level app development, privacy issues, and guideline for the developers about what measure they should consider while developing apps. We also discussed the historical development of Android OS and the end-users role to maintain privacy and to minimize security risks.